Aldosterone induces trained immunity: the role of fatty acid synthesis. Issue 2 (22nd May 2019) - van der Heijden, Charlotte D C C; Keating, Samuel T; Groh, Laszlo; Joosten, Leo A B; Netea, Mihai G; Riksen, Niels P
Abstract: Aims: Supranormal levels of aldosterone are associated with an increased cardiovascular risk in humans, and with accelerated atherosclerosis in animal models. Atherosclerosis is a low-grade inflammatory disorder, with monocyte-derived macrophages as major drivers of plaque formation. Monocytes can adopt a long-term pro-inflammatory phenotype after brief stimulation with microbial pathogens or endogenous atherogenic lipoproteins via a process termed trained immunity . In this study, we aimed to investigate whether aldosterone can induce trained immunity in primary human monocytes in vitro and explored the underlying mechanism. Methods and results: We exposed human monocytes to aldosterone for 24 h, after which they were rested to differentiate into monocyte-derived macrophages for 5 days, and re-stimulated with toll-like receptor 2 and 4 ligands on day 6. We demonstrated that aldosterone augments pro-inflammatory cytokine production and reactive oxygen species production in monocyte-derived macrophages after re-stimulation, via the mineralocorticoid receptor. Fatty acid synthesis was identified as a crucial pathway necessary for this induction of trained immunity and pharmacological inhibition of this pathway blunted aldosterone-induced trained immunity. At the level of gene regulation, aldosterone promoted enrichment of the transcriptionally permissive H3K4me3 modification at promoters of genes central to the fatty acid synthesis pathway. Conclusion: Aldosterone induces trained immunity in vitro, which is dependent on epigenetically mediated up-regulation of fatty acid synthesis. These data provide mechanistic insight into the contribution of aldosterone to inflammation, atherosclerosis, and cardiovascular disease. Graphical Abstract: